COMMUNICATIVE FUNCTIONS AND IMPLICATIONS OF SILENCE IN ENGLISH AND UZBEK (Journal of Universal Science Research, 2025)
Silence is a potent instrument for communication that differs greatly between cultures. This article explores the operation of silence as a communication tool and affects of it in English and Uzbek interpersonal communications. The article emphasizes the value of contextual awareness in cross-cultural communication by examining the realization and usage of silence in both cultures.